Improving the Quality of Natural and Social Sciences (IPAS) Learning through a Socio-Scientific Approach to Critical Thinking and Learning Motivation - Dewa Putu Reza Setiawan; I Wayan Kertih; I Wayan Widiana (Universitas Pendidikan Ganesha, 2025)
Science learning in elementary schools still faces challenges, including low critical thinking skills and low student motivation, due to the dominance of less context-rich, less meaningful learning. This condition demands a learning transformation in line with the Independent Curriculum and the strengthening of 21st-century skills. This study aims to analyze, evaluate, and test the effect of implementing the Socio-Scientific Issue (SSI)-oriented RADEC learning model on students' critical thinking skills and motivation to learn science. The study used a quantitative, quasi-experimental design. The research subjects were fifth-grade elementary school students, with a total population of 365 students and a research sample of 51 students. Data collection was carried out using both test and non-test methods, with multiple-choice test instruments. Data analysis was carried out using descriptive and inferential statistics, including MANOVA and one-way ANOVA. The results showed that implementing the SSI-oriented RADEC learning model significantly improved students' critical thinking skills and motivation to learn science. The experimental group demonstrated higher mean scores in both critical thinking skills and learning motivation compared to the control group. The study's conclusion confirms that the SSI-oriented RADEC model is effective in addressing students' low critical thinking skills and motivation to learn science. The research findings confirm that this model can serve as a strategic alternative for teachers in designing science and science learning.